Persentase Karkas Dan Giblet Burung Puyuh (Coturnix-Coturnix Japonica) Betina Fase Layer Yang Diberi Ekstrak Buah Pare - Ega Gumilar Rahayu; H Nur; Jatmiko Jatmiko (Musamus Journal of Livestock Science, 2020)
Bitter melon (Momordica charantia) is a vine plant with fruits having oblong-shaped fruits which have distinct warty exterior and bitter taste. The fruits are known to have an antibiotic benefit. This study was aimed at assessing the effects of the inclusion of bitter melon fruit extract in drink water on carcass and giblet percentages of quails. The study was conducted at the Trial Farm of Department of Animal Science, Djuanda University, Bogor, in February to March 2019. One-hundred female quails aged 37 days were used. The birds were allocated to 20 units of pens and each pen was occupied by 5 birds. A completely randomized design with 5 treatments and 4 replicates was used. Treatments consisted of 0% bitter melon fruit extract (R0, control), 2.5% bitter melon fruit extract (R1), 5.0% bitter melon fruit extract (R2), 7.5% bitter melon fruit extract (R3), and 10.0% bitter melon fruit extract (R4). Data were subjected to an analysis of variance (Anova) and a Duncan test. Measurements were taken on live weight, carcass weight, gizzard weight, liver weight, and heart weight. Results showed that treatments did not give any significant effects on carcass and giblet percentages. It was suggested that for future studies, nutrient content analysis on bitter melon be conducted beforehand.